Effects of Climate Change on the Immune System: A Narrative Review - Luisa Imberti; Giorgio Tiecco; Jacopo Logiudice; Francesco Castelli; Eugenia Quiros‐Roldan (Health Science Reports)
ABSTRACT Background and Aims Human activities have greatly influenced global temperatures, leading to climate change and global warming. This narrative review aims to explore the relationship between climate change and the immune system, focusing on how environmental stressors can affect immune regulation, leading to both hyperactivity and suppression. Methods A comprehensive search was conducted in PubMed and Google Scholar for peer‐reviewed studies published up to June 2024. The search terms included “climate change,” “human health,” “infection,” “immunity,” and “disease.” Inclusion criteria were based on relevance, originality, and accessibility. Results Exposure to elevated temperatures can significantly impair immune system cells, leading to an overproduction of signaling molecules that promote inflammation. Temperature fluctuations have been shown to influence various aspects of the adaptive immune response, including immune cell mobilization, antigen processing and presentation, lymphocyte trafficking and activation, and the functionality of B and T cells. Notably, some research suggests that heat stress negatively impacts B lymphocyte differentiation, replication, and proportion, resulting in decreased immunoglobulin and cytokine production, and contributing to immunosuppression. Additionally, climate change‐related exposures can compromise epithelial barriers in the skin, lungs, and gut, leading to microbial dysbiosis, and immune dysregulation. Furthermore, environmental factors such as temperature variations, humidity, and air pollutant levels may exacerbate the prevalence of infectious diseases, including measles and HIV, with varying impacts on acute, chronic, and latent infections, further contributing to immune variability. Conclusion Climate change, particularly increased temperatures, significantly impacts immune system function, leading to both heightened inflammatory responses, and immunosuppression. Future research should focus on developing comprehensive and sustainable management strategies to enhance health resilience in the face of ongoing climatic changes.